2014
DOI: 10.1371/journal.pone.0081981
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Audio Computer Assisted Self-Interview and Face-To-Face Interview Methods in Eliciting HIV-Related Risks among Men Who Have Sex with Men and Men Who Inject Drugs in Nigeria

Abstract: IntroductionFace-to-face (FTF) interviews are the most frequently used means of obtaining information on sexual and drug injecting behaviours from men who have sex with men (MSM) and men who inject drugs (MWID). However, accurate information on these behaviours may be difficult to elicit because of sociocultural hostility towards these populations and the criminalization associated with these behaviours. Audio computer assisted self-interview (ACASI) is an interviewing technique that may mitigate social desira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…Injecting drug use in the past month was reported to be 7.7% among MSM in Nigeria. 75 Prevalence of drug use in the past 3 months ranged from 1.4% for MSM in Kenya 18 to 13.9% for MSM in Tanzania. 76 The 6-month and past year range is 0.0% in Botswana 39 to 12.2% in Malawi, 77 and 0.7% in Tanzania 74 to 7.7% in Lesotho, 63 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injecting drug use in the past month was reported to be 7.7% among MSM in Nigeria. 75 Prevalence of drug use in the past 3 months ranged from 1.4% for MSM in Kenya 18 to 13.9% for MSM in Tanzania. 76 The 6-month and past year range is 0.0% in Botswana 39 to 12.2% in Malawi, 77 and 0.7% in Tanzania 74 to 7.7% in Lesotho, 63 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A study among Nigerian MSM indicated the importance of assessment procedures: with Audio Computer-Assisted Self-Interviewing (ACASI), the reported injection drug use was 40 times higher than in face-to-face interviews. 75 Baral et al 77 reported that almost one in five MSM were not willing to answer a question about injecting drug use.…”
Section: Resultsmentioning
confidence: 99%
“…The CHW completed the survey using Audio Computer-Assisted Self-Interview (ACASI), which offers protection of confidentiality while reducing social desirability and pressure during assessment (Adebajo et al, 2014). The participant listened to the survey questions read in the audio system (also shown on the screen) and directly entered the responses into a laptop computer.…”
Section: Methodsmentioning
confidence: 99%
“…This social desirability bias could be mitigated in the future through the use of computer-assisted self-interviews. [22][23][24] The unique object multiplier relies on separate, accurate reporting of keychains given out by distributors and keychains received by KP. We cannot know for certain whether all keychains that were said to be distributed were actually given, that individuals received only one keychain each, or how many keychain recipients were simply ineligible for the survey.…”
Section: Discussionmentioning
confidence: 99%